Antimicrobial Properties of Copper Nanoparticles and Amino Acid Chelated Copper Nanoparticles Produced by Using a Soya Extract - I. DeAlba-Montero; Jesús Guajardo-Pacheco; Elpidio Morales-Sánchez; Rene Araujo-Martínez; G. M. Loredo-Becerra; Gabriel-Alejandro Martínez-Castañón; Facundo Ruiz; M. E. Compeán Jasso (Bioinorganic Chemistry and Applications)
This paper reports a comparison of the antibacterial properties of copper-amino acids chelates and copper nanoparticles against Escherichia coli, Staphylococcus aureus, and Enterococcus faecalis. These copper-amino acids chelates were synthesized by using a soybean aqueous extract and copper nanoparticles were produced using as a starting material the copper-amino acids chelates species. The antibacterial activity of the samples was evaluated by using the standard microdilution method (CLSI M100-S25 January 2015). In the antibacterial activity assays copper ions and copper-EDTA chelates were included as references, so that copper-amino acids chelates can be particularly suitable for acting as an antibacterial agent, so they are excellent candidates for specific applications. Additionally, to confirm the antimicrobial mechanism on bacterial cells, MTT assay (3-[4,5-dimethylthiazol-2-yl]-2,5-diphenyltetrazolium bromide) was carried out. A significant enhanced antimicrobial activity and a specific strain were found for copper chelates over E. faecalis. Its results would eventually lead to better utilization of copper-amino acids chelate for specific application where copper nanoparticles can be not used.